2017
DOI: 10.5152/eurjbiol.2017.1703
|View full text |Cite
|
Sign up to set email alerts
|

An Antioxidant Combination Improves Histopathological Alterations and Biochemical Parameters in D-Galactosamine- Induced Hepatotoxicity in Rats

Abstract: The protective effects of a combination of antioxidants on histopathological changes and biochemical parameters were examined in D-galactosamine (D-GaIN)-induced hepatotoxicity in rats. Physiological saline solution was injected intraperitoneally into the control group, while D-GaIN (500 mg kg-1) was administered intraperitoneally into the experimental animals. The combination of 100 mg/kg/day ascorbic acid, 100 mg/kg/day alpha tocopherol, 15 mg/kg/day beta carotene, and 0.2 mg/kg/day sodium selenate was admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…In our work, intraperitoneal injection of 500 mg·kg −1 d ‐GalN resulted in serious hepatocellular injury. The impairment was exhibited as escalation of hepatic enzymes, along with histopathological alterations in the liver tissue of the d ‐GalN‐induced animals, as discussed in our preceding work …”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In our work, intraperitoneal injection of 500 mg·kg −1 d ‐GalN resulted in serious hepatocellular injury. The impairment was exhibited as escalation of hepatic enzymes, along with histopathological alterations in the liver tissue of the d ‐GalN‐induced animals, as discussed in our preceding work …”
Section: Discussionsupporting
confidence: 58%
“…In the antioxidant network system, antioxidant vitamins (ascorbic acid, β‐carotene, α‐tocopherol, and vitamin U) and antioxidant metals/elements (selenium, vanadium, and zinc), respectively, scavenge free radical and act as enzymes' cofactors . Ascorbic acid, β‐carotene, α‐tocopherol as well as selenium presumably deter oxidation/breakdown of neuronal membranes . In general, antioxidants stabilize cell membranes (particularly, neuronal membranes) by counteracting lipid peroxidation .…”
Section: Introductionmentioning
confidence: 99%
“…It was previously suggested that p53 stimulate BAD and promote apoptosis through cytochrome c release from mitochondria in cancer cells (33). Protective effects of selenium and quercetin with other antioxidants were previously reported in biological systems (34)(35)(36)(37)(38)(39). The combination of both molecules in chemotherapy treatment may reduce the damage and accelerate the repairing process caused by chemotherapy.…”
Section: Discussionmentioning
confidence: 81%
“…Catal et al [ 244 ] used the same injury model using D-GaIN to test the effects of antioxidant supplementation (100 mg/kg/day ascorbic acid +100 mg/kg/day α-tocopherol + 15 mg/kg/day β-carotene + 0.2 mg/kg/day sodium selenite) in the liver. The study described four groups: control, control + antioxidants, D-GaIN and D-GaIN + antioxidants.…”
Section: Third Issue: Bioavailability Of Natural Antioxidants and The...mentioning
confidence: 99%